(untitled) (Revista Crioula, 2020)
The focus of this essay is to comment on MONUMENTO À VAIA, written in 1972 to compose Navilouca, an almanac organized by Torquato Neto and Waly Salomão. It consists of VIVA VAIA - Magnum Opus by the concrete poet Augusto de Campos, inspired by the boo received by Caetano Veloso at the III International Song Festival, in 1968. The contributions of CAMPOS (1993) and VELOSO (1997) were mainly used.